On the risks of good intentions and poor evidence – comment on “Back to the future? Conservative grassland management can preserve soil health in the changing landscapes of Uruguay” by Säumel et al. (2023) - J. Paruelo; J. Paruelo; J. Paruelo; L. López-Mársico; P. Baldassini; P. Baldassini; F. Lezama; B. Bazzoni; L. Staiano; A. Nuñez; A. Guido; C. Ríos; et al. (SOIL)
In this article, we make comments on some methodological issues and on the general approach of the paper “Back to the future? Conservative grassland management can preserve soil health in the changing landscapes of Uruguay” (Säumel et al., 2023). We have identified several design and methodological problems in the aforementioned article that may induce potential misinterpretations. First, our concerns are related to aspects of the study design and methodology that, in our opinion, introduce biases and critical errors. Second, we are concerned about the possible interpretations of the study with respect to the design of policies and the development of non-tariff barriers for South American countries.